A Roadmap to Application Integration Using IoT Cloud Platform - B., Meenakshi Sundaram; R. , Thirukkumaran (International Journal of Psychosocial Rehabilitation, 2020)
The Internet of Things (IoT) provides an opportunity to connect all dumb and net-aware physical devices. The cloud helps to store, compute, and do analytics services on a need basis. Providing a storage facility for managing IoT data is more complex. The Cloud IoT platform solves this kind of scalability issue to a great extent. The IoT is all about the sensors; the inter-process correlation of sensors makes a specific application, and it also depends on the divisional components and their pattern of interaction. The cloud IoT platform provides a range of solutions to help with the easy storage and efficient processing of the IoT data. The competent platforms available are Microsoft Azure, Amazon Web Services (AWS), Google Cloud Platform, and IBM Watson. In this paper, we would like to annotate the fundamental components in all these architectures and create a procedural checklist to ease the understanding under one review through broad literature analysis. Secondarily, to substantiate these components, its detailed features are analyzed for its impact. This paper also suggests the guideline mechanism for deriving solutions across different market verticals for application integration using IoT cloud platforms.